(untitled) (Asian Journal of Social Science Studies, 2019)
With the booming popularity of the music industry today, there has been an equally increasing demand for new or refreshing music types. Over the years, this has a resulted in alternative/non-mainstream music genres gradually being accepted as popular music. To cater for the different tastes of music for consumers, in a world where advancement in technology has accelerated globalization to unprecedented levels, music Creators are producing music that have blurred the boundaries between music genres. On the other hand World Music is one that is seen by many as one which is routed in tradition. In that aspect, world music and popular music can be seen as two contrasting categories.